Hadith Research Methodology in the Perspective of Syuhudi Ismail's Thought - Ach. Syafiq Fahmi; Intan Dwi Permatasari; Mas'ud; Faridatul Jannah (Penerbit Hellow Pustaka, 2024)
This research aims to explore and analyze hadith research methodology from the perspective of Syuhudi Ismail, a Muslim scholar known for his contributions to hadith studies. In facing the complexity of contemporary challenges, hadith methodology has an important role in supporting the understanding and dissemination of Islamic teachings. Syuhudi Ismail, with his critical thinking approach, has made a significant contribution to the development of hadith research methodology. This research will identify the methodological principles proposed by Syuhudi Ismail, and explain the context of his thinking, using library research methods. The results of this research state that in Syuhudi Ismail's concept of thought, the object of hadith research is divided into 2, namely sanad research (Naqd al Khariji) and matan research (Naqd al-Dakhiliy). In sanad research (Naqd al Khariji), it begins with carrying out I'tibar al-Sanad and then continues with researching the personalities of the narrators and their methods of narration. In this research on sanad, Syuhudi mentions the elements of the rules for the validity of sanad in the simplified terms